Media and personal and social risk perceptions: the case of covid-19 pandemic in Malaysia - Andreas Totu; Stephen Laison Sondoh Jr.; Romzi Ationg; Halina Sendera Mohd. Yakin; Haryati Abd Karim (2021)
Mass media have long been recognised as powerful forces shaping how we experience and perceive the world. This article aims to look at the role of media, including mass media and social media, in creating people's perception of the risk brought by the virus Covid-19. This paper also discusses the differing impacts of media on risk perceptions from personal and social levels. There are 400 respondents involved, which were taken through an online survey, using Survey Monkey Application. The study uses online questionnaires and the data collected were analysed using SPSS version 27. Specifically, this article contemplates answering two important hypotheses: (1) Gender has a significant effect on risk perceptions, and (2) Media exposure has a stronger effect on social risk perception than on personal risk perception. The results showed that media have a positive role in shaping the perception of the risk of Covid-19 among the respondents. The study outcomes suggest that media exposure has a more substantial effect on social risk perceptions than personal risk perceptions.